Persepsi Mahasiswa terhadap Pembelajaran Daring pada Mata Kuliah Bahasa Inggris di Era Pandemi - Erna Megawati; Priarti Megawanti; Santi Nugraha (Universitas Indraprasta PGRI Jakarta, 2022)
The internet of thing’s centered 4.0 technology revolution changed the face of education. It also encourages the occurrence of decoupling phenomenon. This is when the education can be done everywhere and anywhere. With the challenge, the change becomes inevitability when the world is confronted with a pandemic Covid-19. Descriptive quantitative analysis in this study examines student’s perceptions in the Faculty of Language and Arts Indraprasta PGRI University about the conditions, situations, and event during the online learning. The number of samples in this study were 170 active student’s of the bachelor first class program of Indonesian Language Education school year 2020/2021 which has a special English courses during online learning due to pandemic.The data collections thecnique used is questionnaire throught Google form. The results of the study also showed that 98% of lecturers' perceptions of competence were positive, which means that lecturers' competences are believed to have a positive and significant influence either partially or simultaneously and 95.9% of perceptions of facilities and infrastructure also showed positive results, which means that students believe that aspects of facilities and infrastructure are one of the elements. That affects the learning process and outcomes.